Super-hydrophilic self-cleaning metal / alloy and preparation method thereof
The micro-nanostructures are prepared on the metal/alloy surface through laser scanning, and the ultra-hydrophilic self-cleaning effect is achieved, solving the problem of high cost in the existing technology and ineffective oil and dust, and achieving low-cost and widely used self-cleaning effect.
Patent Information
- Application Number
- CN202311166804.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-14
AI Technical Summary
Existing self-cleaning technologies such as hydrophobic or superhydrophobic coatings are costly and ineffective against grease and dust, and are not cost-effective, making them difficult to widely used in photovoltaic frames, locomotives, aircraft and other scenarios.
Micro-nanostructures are prepared on the metal/alloy surface by laser scanning, changing the superhydrophilicity of the surface so that its affinity with water exceeds that of pollutants and dust, thereby achieving a self-cleaning effect.
It achieves a low-cost, widely used self-cleaning effect. Water can easily penetrate between the super-hydrophilic surface and pollutants. Rainwater takes away pollutants, reduces cleaning and maintenance costs, and has anti-frost function.
Smart Images

Figure CN119609372A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of super-hydrophilic self-cleaning metal / alloy preparation, and prepares corresponding micro-nano structures on the metal / alloy surface by laser scanning to achieve a self-cleaning effect. Background Art
[0002] Currently, the global photovoltaic installed capacity is close to 1TW and is still growing rapidly. After rain, there will be water and dust accumulation around the aluminum alloy frame, causing local hot spots, which may cause breakdown and fire accidents in severe cases. The cleaning and maintenance costs of airplanes, trains, and cars are high, and the cleaning process will also cause a certain degree of wear and tear. Building doors, windows, decorations, etc. are dusty and difficult to clean, and cleaning will cause a certain amount of wear and tear.
[0003] The current mainstream self-cleaning technology uses hydrophobic or super-hydrophobic coatings. The cost is relatively high. In addition, super-hydrophobic coatings are ineffective against grease, dust, etc., and only work on water-soluble pollutants. Therefore, the cost-effectiveness is not high.
[0004] The present invention adopts super-hydrophilic surface technology. The affinity of super-hydrophilic metal / alloy surface to water exceeds the affinity of pollution and dust to super-hydrophilic surface. Therefore, water easily penetrates between super-hydrophilic surface and pollutants and dust. Rainwater takes away the separated pollutants and dust under the action of gravity. This self-cleaning performance can be widely used in photovoltaic frames, locomotives, and aircraft.
[0005] Therefore, the present invention develops super hydrophilic self-cleaning metals / alloys to meet the relevant needs.
[0006] At the same time, the transition from superhydrophilicity to superhydrophobicity can occur naturally without incurring additional costs. It has a certain self-cleaning ability throughout the process. The superhydrophobic surface also has the additional function of anti-frost. Summary of the invention
[0007] The present invention provides a super-hydrophilic self-cleaning metal / alloy and a preparation method thereof, and achieves the purpose of self-cleaning by adjusting the micro-nano structure array on the surface of the metal / alloy by changing the laser scanning parameters.
[0008] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: The invention provides a method for preparing a super-hydrophilic self-cleaning metal / alloy, namely: laser scanning the metal / alloy surface to form a micro-nano structure on the metal / alloy surface to obtain the super-hydrophilic self-cleaning metal / alloy.
[0009] Furthermore, the laser includes at least one of an infrared laser, a visible light laser, an ultraviolet laser, a continuous laser, and a pulsed laser.
[0010] Furthermore, the laser energy density is greater than 30 mJ / cm 2.
[0011] Preferably, the laser scanning uses a 30W rated power ultraviolet laser with a wavelength of 1064 nm. If the laser frequency is 40KHz and the laser spot diameter is 50 microns, the energy density at this time can be estimated to be 38 J / cm 2 .
[0012] Furthermore, the laser scanning speed is 0.01 m / s-500 m / s; the scanning line spacing is ≤100 mm.
[0013] Preferably, the scanning speed of the laser scanning is 1 m / s-10 m / s; the scanning line spacing is 0.03-0.2 mm.
[0014] Furthermore, the super-hydrophilic self-cleaning metal / alloy can be used as the inner surface of the metal / alloy, and can also be used as the outer surface of the metal / alloy.
[0015] Furthermore, the metal / alloy includes all solid metals / alloys.
[0016] Furthermore, the super-hydrophilic self-cleaning metal / alloy surface prepared by the method can be used for photovoltaic aluminum alloy frames and metal / alloy products.
[0017] The present invention also provides another self-cleaning metal / alloy and its preparation method. When the super-hydrophilic self-cleaning metal / alloy prepared above is placed in the air for 2 months, the super-hydrophilic surface automatically becomes a hydrophobic or even a super-hydrophobic surface, and still has a certain self-cleaning performance; Furthermore, the super-hydrophilic metal / alloy can be placed in a vacuum chamber for one night, and the super-hydrophilic surface will automatically become a hydrophobic or even a super-hydrophobic surface, and still have a certain self-cleaning performance; Furthermore, the super-hydrophilic metal / alloy can be placed in a muffle furnace at 250° C. for one hour, and the super-hydrophilic surface will automatically become a hydrophobic or even a super-hydrophobic surface, and still have a certain self-cleaning performance.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can achieve self-cleaning performance by using a simple process, and its cost performance is better than the existing technology. The existing technology is complicated and requires an additional hydrophobic layer to be coated manually.
[0019] 2. The preparation method of the present invention achieves super-hydrophilicity with a contact angle of 0 degrees. The 0-degree super-hydrophilic surface has extremely strong water absorption, and water droplets are easy to spread on it, and fresh water is easy to collect. Super-hydrophilicity facilitates water to penetrate into the surface and separate pollutants, which is conducive to rainwater taking away pollutants and achieving self-cleaning. However, the existing technology uses super-hydrophobic coatings that are ineffective against organic oil pollution and pollutants that can stick to the surface.
[0020] 3. The process is simple, the entire preparation method is low-cost, and can be completed using industrially stable and mature equipment. Therefore, it can be directly used to improve the performance of metals / alloys and produce super-hydrophilic self-cleaning metals / alloys, and has the advantage of scalable production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the surface wetting angle of the metal after treatment in Example 1.
[0022] Figure 2 In Example 1, the methyl orange solution is uniformly sprayed onto the surface of the special sample, one side of the sample is the surface treated by the process of Example 1, and the other side is the reference surface that is not treated by laser.
[0023] Figure 3 This is a surface photograph of a special sample contaminated with methyl orange that was cleaned by uniform water spraying in Example 1.
[0024] Figure 4 This is a SEM photograph of the surface of the treated portion in Example 1.
[0025] Figure 5 This is a confocal microscope photograph of the surface in Example 1.
[0026] Figure 6 This is a photograph of the contact angle of the treated metal in Example 1 after being placed in the air for 2 months to become superhydrophobic.
[0027] Figure 7 is the surface wetting angle of the metal after treatment in Example 2.
[0028] Figure 8 In Example 2, the methyl orange solution is uniformly sprayed onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is a reference surface that has not been treated by laser.
[0029] Fig. 9 This is a surface photograph of a special sample contaminated with methyl orange that was cleaned by uniform water spraying in Example 2.
[0030] Fig.10 This is a photograph of the contact angle of the treated metal in Example 2 after being placed in a vacuum overnight to become superhydrophobic.
[0031] Fig.11 is the surface wetting angle of the metal after treatment in Example 3.
[0032] Fig.12 In Example 3, the methyl orange solution is uniformly sprayed onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been treated by laser.
[0033] Fig.13This is a surface photograph of a special sample contaminated with methyl orange that was cleaned by uniform water spray in Example 3.
[0034] Fig.14 This is a SEM photograph of the surface of the treated portion in Example 3.
[0035] Fig.15 This is a confocal microscope photograph of the surface in Example 3.
[0036] Fig.16 This is a photograph of the contact angle of the treated metal in Example 3 after being placed in a muffle furnace at 250° C. for one hour to become superhydrophobic.
[0037] Fig.17 is the surface wetting angle of the metal after treatment in Example 4.
[0038] Fig.18 In Example 4, the methyl orange solution is uniformly sprayed onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been treated by laser.
[0039] Fig.19 This is a surface photograph of a special sample contaminated with methyl orange that was cleaned by uniform water spray in Example 4.
[0040] Fig. 20 is the surface wetting angle of the metal after treatment in Example 5.
[0041] Fig.21 In Example 5, the methyl orange solution is uniformly sprayed onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is a reference surface that has not been treated by laser.
[0042] Fig. 22 This is a surface photograph of a special sample contaminated with methyl orange that was cleaned by uniform water spray in Example 5.
[0043] Fig.23 is the surface wetting angle of the metal after treatment in Example 6.
[0044] Fig.24 In Example 6, the methyl orange solution is uniformly sprayed onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been treated by laser.
[0045] Fig.25 This is a surface photograph of a special sample contaminated with methyl orange that was cleaned by uniform water spray in Example 6. DETAILED DESCRIPTION
[0046] The following embodiments are used to better illustrate the present invention, but the present invention is not limited to the following embodiments.
[0047] Example 1: Preparation of super hydrophilic self-cleaning aluminum The specific steps are as follows: A fiber laser marking machine is used to scan the aluminum sheet to form a micro-nano structure on the surface of the aluminum sheet. The rated power of the laser is 30W. The parameters of the laser scanning are: scanning speed 10m / s; scanning line spacing 0.03mm; frequency 60khz. At this time, it is assumed that the energy density is 38 J / cm when the spot diameter is 50 microns 2 . The result is super hydrophilic, self-cleaning aluminum. Figure 1 Demonstrated superhydrophilic contact angle of treated metal surface reaching 0 degrees; Figure 2 In order to evenly spray the methyl orange solution onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been laser treated. Figure 3 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the treated super-hydrophilic surface, and it has strong self-cleaning ability. However, a large amount of methyl orange still remains on the untreated surface, and it has no self-cleaning ability. Figure 4 From the SEM photograph of the treated surface, it can be seen that nanoparticles of about 100 nm are widely distributed on the treated surface. Figure 5 The confocal microscope photo of its surface shows that there are shallow stripes on its surface and there are widely distributed round pits of varying depths with a diameter of about 50 microns. The stripes and round pits are quasi-periodically distributed. This micro-nanostructure contributes to the super-hydrophilic contact angle of 0 degrees, so the actual self-cleaning effect is good, such as Figure 3 These micro-nano structures play a self-cleaning role according to the self-cleaning theory. Figure 6 To process the contact angle photo of the metal becoming super hydrophobic after being placed in the air for 2 months, it still has certain self-cleaning properties.
[0048] Example 2: Preparation of super hydrophilic self-cleaning copper The specific steps are as follows: A fiber laser marking machine is used to scan a metal copper sheet to form a micro-nano structure on the surface of the copper sheet; the rated power of the laser is 30W; the parameters of the laser scanning are: scanning speed 6m / s; scanning line spacing 0.03mm; frequency 60khz. Super hydrophilic and self-cleaning copper is obtained. Figure 7 Demonstrated superhydrophilic contact angle of treated metal surface reaching 0 degrees; Figure 8 In order to evenly spray the methyl orange solution onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been laser treated. Fig. 9 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the treated super-hydrophilic surface, and it has strong self-cleaning ability. However, a large amount of methyl orange still remains on the untreated surface, and it has no self-cleaning ability. Fig.10 To process the contact angle photo of the metal becoming super hydrophobic after being placed in a vacuum overnight, it still has certain self-cleaning properties.
[0049] Example 3: Preparation of super hydrophilic self-cleaning nickel The specific steps are as follows: A fiber laser marking machine is used to scan a metal nickel sheet to form a micro-nano structure on the surface of the nickel sheet; the laser has a rated power of 30W; the laser scanning parameters are: scanning speed 8m / s; scanning line spacing 0.03mm; frequency 60khz. Super hydrophilic and self-cleaning nickel is obtained. Fig.11 The superhydrophilic contact angle of the treated metal surface was shown to be close to 0 degrees; Fig.12 In order to evenly spray the methyl orange solution onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been laser treated. Fig.13 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the treated super-hydrophilic surface, and it has strong self-cleaning ability. However, a large amount of methyl orange still remains on the untreated surface, and it has no self-cleaning ability. Fig.14 From the SEM photograph of the treated surface, it can be seen that nanoparticles of about 100 nm are widely distributed on the treated surface. Fig.15 The confocal microscope photo of its surface shows that there are shallow stripes on its surface and there are widely distributed round pits of varying depths with a diameter of about 50 microns. The stripes and round pits are quasi-periodically distributed. This micro-nanostructure contributes to the super-hydrophilic contact angle of 0 degrees, so the actual self-cleaning effect is good, such as Fig.13 . Fig.16 To treat the contact angle photo of the metal after being placed in a muffle furnace at 250°C for one hour, it becomes superhydrophobic and still has certain self-cleaning properties.
[0050] Example 4: Preparation of super hydrophilic self-cleaning platinum The specific steps are as follows: A fiber laser marking machine is used to scan the metal molybdenum sheet to form a micro-nano structure on the surface of the molybdenum sheet; the laser rated power is 30W; the laser scanning parameters are: scanning speed 10m / s; scanning line spacing 0.06mm; frequency 60khz. Super hydrophilic and self-cleaning molybdenum is obtained. Fig.17 Demonstrated superhydrophilic contact angle of treated metal surface reaching 0 degrees; Fig.18 In order to evenly spray the methyl orange solution onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been laser treated. Fig.19 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the treated super-hydrophilic surface, and it has strong self-cleaning ability. However, a large amount of methyl orange still remains on the untreated surface, and it has no self-cleaning ability.
[0051] Example 5: Preparation of super hydrophilic self-cleaning titanium The specific steps are as follows: A fiber laser marking machine is used to scan a titanium sheet to form a micro-nano structure on the surface of the titanium sheet. The rated power of the laser is 30W. The parameters of the laser scanning are: scanning speed 5m / s; scanning line spacing 0.03mm; frequency 60khz. Super hydrophilic and self-cleaning titanium is obtained. Fig. 20 The superhydrophilic contact angle of the treated metal surface was shown to be close to 0 degrees; Fig.21 In order to evenly spray the methyl orange solution onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been laser treated. Fig. 22 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the treated super-hydrophilic surface, and it has strong self-cleaning ability. However, a large amount of methyl orange still remains on the untreated surface, and it has no self-cleaning ability.
[0052] Example 6: Preparation of super hydrophilic self-cleaning stainless steel The specific steps are as follows: A fiber laser marking machine is used to scan a metal stainless steel sheet to form a micro-nano structure on the surface of the stainless steel sheet; the laser rated power is 30W; the laser scanning parameters are: scanning speed 4m / s; scanning line spacing 0.08mm; frequency 60khz. Super hydrophilic and self-cleaning stainless steel is obtained. Fig.23 Demonstrated superhydrophilic contact angle of treated metal surface reaching 0 degrees; Fig.24 In order to evenly spray the methyl orange solution onto the surface of the special sample, one side of the sample is the surface treated by the above process, and the other side is the reference surface that has not been laser treated. Fig.25 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the treated super-hydrophilic surface, and it has strong self-cleaning ability. However, a large amount of methyl orange still remains on the untreated surface, and it has no self-cleaning ability.
[0053] The above embodiments illustrate that the properties of metals can be changed by adjusting the laser scanning process parameters, thus having the advantage of being scalable for production. The metal obtained by the above preparation method of the present invention has super hydrophilic and self-cleaning properties and can be used to produce photovoltaic aluminum alloy frames, metal / alloy products, seawater desalination, and nuclear energy pipelines.
[0054] In addition, the treated metal surface can be used as the inner surface of the metal used, or as the outer surface.
[0055] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A super-hydrophilic self-cleaning metal / alloy and a preparation method thereof, characterized in that: Laser scanning of the metal / alloy surface forms a micro-nano structure on the metal / alloy surface to obtain a super-hydrophilic self-cleaning metal / alloy.
2. The method for preparing a super-hydrophilic self-cleaning metal / alloy according to claim 1, characterized in that: The laser includes at least one of an infrared laser, a visible light laser, an ultraviolet laser, a continuous laser, and a pulsed laser.
3. The method for preparing a super-hydrophilic self-cleaning metal / alloy according to claim 1, characterized in that: The laser energy density is greater than 30 mJ / cm 2 .
4. The method for preparing a super-hydrophilic self-cleaning metal / alloy according to claim 1, characterized in that: The metals / alloys include all solid metals / alloys.
5. A super-hydrophilic self-cleaning metal / alloy and a method for preparing the same, characterized in that: The super hydrophilic self-cleaning metal / alloy prepared according to claim 1 becomes hydrophobic or even super hydrophobic after being placed in the air for 2 months, and still has a certain self-cleaning performance.
6. A super-hydrophilic self-cleaning metal / alloy and a method for preparing the same, characterized in that: The super hydrophilic self-cleaning metal / alloy prepared according to claim 1 becomes hydrophobic or even super hydrophobic after being placed in a vacuum overnight, and still has a certain self-cleaning performance.
7. A super-hydrophilic self-cleaning metal / alloy and a method for preparing the same, characterized in that: The super hydrophilic self-cleaning metal / alloy prepared according to claim 1 becomes hydrophobic or even super hydrophobic after being placed in a muffle furnace at 250° C. for one hour, and still has certain self-cleaning performance.
8. The super-hydrophilic self-cleaning metal / alloy prepared by the preparation method according to any one of claims 1 to 7 and its application. Characterized in that: The super-hydrophilic self-cleaning metal / alloy can be used as the inner surface of glass, and can also be used as the outer surface of metal / alloy.
Citation Information
Patent Citations
Bionic metal ultra-wetting trans-scale structure design method and preparation method
CN101712102A
Laser manufacturing method for super-hydrophilic titanium alloy heat exchange plate
CN107252978A
Titanium alloy super hydrophobic-super hydrophilic surface and preparing method and application of titanium alloy super hydrophobic-super hydrophilic surface
CN109732195A
Method for preparing, regulating and controlling super-hydrophobic / super-hydrophilic reversible regulation metal surface
CN110029349A
Method for preparing super-hydrophilic amorphous alloy surface through nanosecond laser irradiation
CN113308657A